Understanding parental influence on toddler task persistence: autonomy support, control, praise, and feedback - Lim, Suki Shuqi (Nanyang Technological University, 2024)
This study investigates the relationship between parental behaviours – specifically autonomy support, control, praise (including process, person, and ambiguous praise), and criticism (including process, person criticism and corrective feedback) – and toddlers’ task persistence during challenging tasks. A sample of 40 parent-toddler dyads participated in a laboratory-based observational study, with toddlers aged 16 to 18 months. Video recordings of parent-toddler interactions during easy and hard barn tasks were coded for parental behaviours, and Spearman's correlation analysis was conducted to examine their associations with toddler task persistence. Results indicate a significant positive correlation between parental autonomy support, process praise, and toddler task persistence during the hard barn phase. A positive correlation was also found between parental control and toddlers’ task persistence during the hard barn phase, challenging the initial hypothesis. No significant correlations were observed between ambiguous praise, person praise, process criticism, and toddlers’ task persistence during the hard barn phase. The study also unveiled a significant positive correlation between overall parental praise and toddlers’ task persistence for both easy and hard barn phases. Conversely, no significant correlations were found between overall parental criticism and toddlers’ task persistence. Moreover, the study failed to identify any significant correlation between parental tone of voice (whether positive, neutral and negative) during criticism and toddlers’ task persistence. These findings highlight the complex nature of parent-child interactions and underscore the need for further research to elucidate the mechanisms underlying these dynamics.